Application of a cashew-based oxime in extracting Ni, Mn and Co from aqueous solution - Phan, Chi; Hoang, S.A.; Vu, S.H.; Nguyen, H.M.; Nguyen, C.V.; Hyde, Anita; Yusa, S.I. (SPRINGER, 2021)
Background: Cashew nut shell is a by-product of cashew (Anacardium occidentale) production, which is abundant in many developing countries. Cashew nut shell liquor (CNSL) contains a functional chemical, cardanol, which can be converted into a hydroxyoxime. The hydroxyoximes are expensive reagents for metal extraction.